2010
DOI: 10.1097/mbc.0b013e32833c2b52
|View full text |Cite
|
Sign up to set email alerts
|

Novel management of post varicella purpura fulminans owing to severe acquired protein S deficiency

Abstract: Acquired protein S deficiency is a rare complication of varicella zoster infection often resulting in purpura fulminans, which is a potentially life-threatening syndrome of intravascular thrombosis and haemorrhagic infarction of the skin. Patients are presumed to develop crossreacting autoantibodies to the virus and protein S. There is no consensus on how best to manage these patients but previous recommendations focus on plasmapheresis and plasma exchange. We report the case of a 3-year-old girl with post var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 11 publications
1
7
0
1
Order By: Relevance
“…Indeed, such a postinfection decrease of PC/PS activity that resolved within 6-9 months after the Pediatric Hematology and Oncology Skin Necrosis and Purpura With/Without Thrombophilia  acute event was observed in 3 of our patients. Whereas varicella-associated anti-PS antibodies (causing transient PS deficiency in one of our cases) were previously reported [23][24][25], other infections within our cohort (e.g., pneumococcal sepsis, undefined viral infection) had a similar impact.…”
Section: Discussionmentioning
confidence: 58%
“…Indeed, such a postinfection decrease of PC/PS activity that resolved within 6-9 months after the Pediatric Hematology and Oncology Skin Necrosis and Purpura With/Without Thrombophilia  acute event was observed in 3 of our patients. Whereas varicella-associated anti-PS antibodies (causing transient PS deficiency in one of our cases) were previously reported [23][24][25], other infections within our cohort (e.g., pneumococcal sepsis, undefined viral infection) had a similar impact.…”
Section: Discussionmentioning
confidence: 58%
“…Shah et al (11) explained a rare association of purpura fulminans with West Nile Virus infection. Thomson et al (12) reported varicella zoster infection in a patient that progressed to PF. Antibodies against protein S occur, and protein S deficiency induced by varicella-zoster infection can be the etiology of PF in this patient (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…Thomson et al (12) reported varicella zoster infection in a patient that progressed to PF. Antibodies against protein S occur, and protein S deficiency induced by varicella-zoster infection can be the etiology of PF in this patient (12,13). According to research that assessed maternal deaths due to infectious cause, there was a significant association between the influenza A (H1N1) virus and purpura fulminans (14).…”
Section: Discussionmentioning
confidence: 99%
“…PS is an essential cofactor for activated PC, one of the major regulators of hemostasis, which when activated by thrombin/ In children, post infectious PF associated with VZV is welldocumented in the literature. [10][11][12][15][16][17][18][19][20][21][22][23] In these cases, varicella infection has been shown to induce autoantibody formation that results in lowering of both PS total and free antigen. 10,11,20 A variety of mechanisms have implicated infectious agents in the induction of autoimmune diseases, with "molecular mimicry" being the prevailing theory.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, most reported cases of post varicella PF from low PS in the literature document very disproportionately low PS levels in comparison to PC levels. 10,12,17,19,23 Some PC levels have even been documented to be normal. 10,15,20,22 The Levin et al 10 case series is particularly illustrative, where post infectious PF occurred with essentially undetectable free PS levels and relatively preserved PC activity levels in all 5 patients.…”
Section: Discussionmentioning
confidence: 99%